Interaction of combined loads on the lateral stability of thin-walled composite beams - Machado, Sebastián Pablo (2010)
Based on a seven-degree-of-freedom shear deformable beam model, analytical solutions are derived for the lateral stability analysis of cross-ply laminated thin-walled beams subjected to combined axial and bending loads. The model includes shear deformability in a full form, i.e. shear flexibility due to both bending and nonuniform warping is considered. The theory is formulated in the context of large displacements and rotations, considering moderate bending rotations and large twist. Composite is assumed to be made of symmetric balanced laminates and especially orthotropic laminates. The closed-form analytic expressions obtained in this paper are valid for simply supported bisymmetric beams. These fundamental solutions explicitly identify the influence of geometric nonlinear effects due to the prebuckling deformation. The numerical results are compared with the bifurcation loads of the postbuckling response. In addition, the effects of the variation of load height parameter and fiber angle orientation are investigated. © 2010 Elsevier Ltd.